2022
DOI: 10.1017/s0033291722003269
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in regional gray matter density in pre-adolescent binge eating disorder: a voxel-based morphometry study

Abstract: Background Binge eating disorder (BED) is a pernicious psychiatric disorder which is linked with broad medical and psychiatric morbidity, and obesity. While BED may be characterized by altered cortical morphometry, no evidence to date examined possible sex-differences in regional gray matter characteristics among those with BED. This is especially important to consider in children, where BED symptoms often emerge coincident with rapid gray matter maturation. Methods Pre-adolescent, 9–10-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…This work might also consider how findings vary across dimensions of depression, such as anhedonia. Indeed, prior work has established a particular association of anhedonia with both higher instability and lower intensity of positive affect in adolescence (Murray et al, 2022). Although this factor has not been specifically identified within the CES‐DC (as used in our study; Barkmann et al, 2008), future investigations might use other measures to examine this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…This work might also consider how findings vary across dimensions of depression, such as anhedonia. Indeed, prior work has established a particular association of anhedonia with both higher instability and lower intensity of positive affect in adolescence (Murray et al, 2022). Although this factor has not been specifically identified within the CES‐DC (as used in our study; Barkmann et al, 2008), future investigations might use other measures to examine this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the landmark Adolescent Brain Cognitive Development℠ Study (ABCD Study®), the largest long‐term study of brain development in the United States (ABCD Study, 2022 ), enrolled over 11,800 9‐ and 10‐year‐old children to further study biological and social factors, like gender on brain development (Volkow et al, 2018 ). As such, several recent studies using ABCD data have reported significant neuroanatomical sex differences across numerous domains, including subcortical volume (Adeli et al, 2020 ), cortical thickness (Brennan et al, 2021 ; Tomasi & Volkow, 2023 ; Wiglesworth et al, 2023 ), gray matter density (Murray et al, 2022 ), white matter microstructure (Lawrence et al, 2023 ; Tomasi & Volkow, 2023 ), and differences in the association between brain structure and behavior (Chen et al, 2022 ; Kim et al, 2022 ). However, none of these previous studies on sex differences utilizing the ABCD study examined the potential role of gender.…”
Section: Introductionmentioning
confidence: 99%
“…Por lo que respecta a los factores biológicos, los estudios sobre genética han concluido que la heredabilidad de los TCA es alta (Rojo et al, 2017). Otros estudios apuntan a que los TCA estarían elicitados parcialmente por una desconexión entre las redes de control inhibitorio y de recompensa en el cerebro (Murray et al, 2022a) o por diferentes intersexuales en la materia gris cerebral (Murray et al, 2022b).También, en relación con los mecanismos biológicos, cabe señalar la existencia de numerosos estudios (Babio et al, 2009;Espinoza et al, 2010;Gutiérrez et al, 2015) que proponen el Índice de Masa Corporal (IMC en adelante) como predictor de los TCA, teniendo en cuenta su relación con la obesidad. Así, un IMC alto sería un factor de riesgo para la aparición de TCA (Espinoza et al, 2010).…”
Section: Introductionunclassified